2021
DOI: 10.1186/s12963-021-00260-5
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of 2017 ACC/AHA guideline on prevalence, awareness, treatment, control, and determinants of hypertension: a population-based cross-sectional study in southwest of Iran

Abstract: Background In 2017, the American College of Cardiology/American Heart Association (ACC/AHA) provided a new guideline for hypertension prevention and management. We aimed to update the prevalence, awareness, control, and determinants of hypertension based on this guideline in Khuzestan province, southwest of Iran, and to estimate the number of people who are eligible for non-pharmacologic and pharmacologic intervention. Methods This population-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Another study across 16 Iranian provinces projected an increase in age-sex standardized prevalence from 22.3-36.5% 20 . In Tehran 22 , Yazd 23 , and Khuzestan 24 , hypertension prevalence was estimated to change from 20.4-47.1%, 28.9-61.0%, and dramatically from 15.81-42.85% with ACC/AHA adoption instead of JNC7. Internationally, adopting the ACC/AHA guideline in China doubled hypertension prevalence 25 , and also showed a steeper trend, while Brazil experienced a 2.6-fold increase, from 21.1-54.7% 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study across 16 Iranian provinces projected an increase in age-sex standardized prevalence from 22.3-36.5% 20 . In Tehran 22 , Yazd 23 , and Khuzestan 24 , hypertension prevalence was estimated to change from 20.4-47.1%, 28.9-61.0%, and dramatically from 15.81-42.85% with ACC/AHA adoption instead of JNC7. Internationally, adopting the ACC/AHA guideline in China doubled hypertension prevalence 25 , and also showed a steeper trend, while Brazil experienced a 2.6-fold increase, from 21.1-54.7% 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle modi cations are recommended before reaching these thresholds. Therefore, the transition from JNC7 to ACC/AHA is expected to have a limited impact on medication prescriptions, as previous studies in Iran demonstrated only marginal increases of about 21.18% 24 and 30% 21 after the shift, resulting in only slightly higher costs for the health system. However, in other countries such as the US and China, this change was associated with signi cantly higher costs 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors reported a missing grant number in their Funding declaration. The updated Funding declaration is as follows:…”
Section: Correction To: Population Health Metrics (2021) 19:26 101186/s12963-021-00260-5mentioning
confidence: 99%
“…A number of studies have looked into the epidemiological consequences of changing the definitions from ≥140/90 to ≥130/80 mm Hg to define hypertension in specific regions or countries, including the United States, 14,15 China, 15 Australia, 16 Iran, 17 and Saudi Arabia 18 among others. However, some of these reports are limited to narrow age ranges or specific ethnic groups, which reduces comparability.…”
mentioning
confidence: 99%